Osmotic Adjustment in Cotton (Gossypium hirsutum L.) Leaves and Roots in Response to Water Stress - Oosterhuis, Derrick M. (1987)
The relative magnitude of adjustment in osmotic potential (ψ(s)) of water-stressed cotton (Gossypium hirsutum L.) leaves and roots was studied using plants raised in pots of sand and grown in a growth chamber. One and three water-stress preconditioning cycles were imposed by withholding water, and the subsequent adjustment in solute potential upon relief of the stress and complete rehydration was monitored with thermocouple psychrometers. Both leaves and roots exhibited a substantial adjustment in ψ(s) in response to water stress with the former exhibiting the larger absolute adjustment. The osmotic adjustment of leaves was 0.41 megapascal compared to 0.19 megapascal in the roots. The roots, however, exhibited much larger percentage osmotic adjustments of 46 and 63% in the one and three stress cycles, respectively, compared to 22 and 40% in the leaves in similar stress cycles. The osmotically adjusted condition of leaves and roots decreased after relief of the single cycle stress to about half the initial value within 3 days, and to the well-watered control level within 6 days. In contrast, increasing the number of water-stress preconditioning cycles resulted in significant percentage osmotic adjustment still being present after 6 days in roots but not in the leaves. The decrease in ψ(s) of leaves persisted longer in field-grown cotton plants compared to plants of the same age grown in the growth chamber. The advantage of decreased ψ(s) in leaves and roots of water-stressed cotton plants was associated with the maintenance of turgor during periods of decreasing water potentials.